RNA-activated protein kinase differentially modulates innate immune response mediated by supraphysiological concentrations of thyroid hormone. Issue 8 (November 2020) - Ishaq, Mohammad; Natarajan, Ven
Nuclear hormone receptor ligands are known to modulate innate immunity by dampening the immune response induced by pathogens. Here, we report that unlike other ligands, 3, 3′, 5-triiodo-l -thyronine (T3) induced the type 1 IFN response and expression of IFN-stimulated genes (ISGs). T3 action was found to be significantly amplified at supraphysiological concentrations (SPC) and in combination with double-stranded RNA mimic polyinosinic–polycytidylic acid. Induction by T3 was due to non-genomic mechanisms involving integrin binding, calcium mobilization, and phosphatidyl-inositol 3-kinase–AKT pathways, but was independent of TLR3, RIG-I, and IFN-β1 pathways. Whereas siRNA-induced knockdown of RNA-activated protein kinase (PKR) was found to abrogate the T3-induced expression of select ISGs, expression of other T3-induced ISGs was strongly induced by PKR knockdown, indicating the differential role of PKR in modulating T3 action. Together, we describe a novel role of T3 in modulating the innate immune response and identify the importance of PKR in regulating T3-induced immune activation. These findings have important implications in the basic understanding of the mechanisms of T3 function at SPCs and crosstalk involved in the thyroid hormone function and the innate immune response.